2017
DOI: 10.1130/ges01509.1
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the crust and African slab beneath the central Anatolian plateau from receiver functions: New insights on isostatic compensation and slab dynamics

Abstract: The central Anatolian plateau in Turkey is a region with a long history of subduction, continental collision, accretion of continental fragments, and slab tearing and/or breakoff and tectonic escape. Central Anatolia is currently characterized as a nascent plateau with widespread Neogene volcanism and predominantly transtensional deformation. To elucidate the present-day crustal and upper mantle structure of this region, teleseismic receiver functions were calculated from 500 seismic events recorded on 92 temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(98 citation statements)
references
References 63 publications
7
77
0
Order By: Relevance
“…The latter mechanism is consistent with the thick Anatolian crust and lithosphere and the presence of the Cyprus slab under the modern Central Taurus Mountains (e.g., Bakırcı et al, 2012;Abgarmi et al, 2017;Delph et al, 2017) and the coupled, short-wavelength vertical motions reported for South Turkey and its offshore during plateau margin growth (Walsh-Kennedy et al, 2014;Fernández-Blanco et al, 2019).…”
Section: First-order Morphotectonic Features In the Current Arc-trencsupporting
confidence: 81%
See 2 more Smart Citations
“…The latter mechanism is consistent with the thick Anatolian crust and lithosphere and the presence of the Cyprus slab under the modern Central Taurus Mountains (e.g., Bakırcı et al, 2012;Abgarmi et al, 2017;Delph et al, 2017) and the coupled, short-wavelength vertical motions reported for South Turkey and its offshore during plateau margin growth (Walsh-Kennedy et al, 2014;Fernández-Blanco et al, 2019).…”
Section: First-order Morphotectonic Features In the Current Arc-trencsupporting
confidence: 81%
“…South Turkey surface uplift and growth of the modern Central Taurus Mountains at ~8 Ma and later times (e.g., Cosentino et al, 2012;Meijers et al, 2018) Thermo-viscous forearc high evolution in relation to mechanical accretion is consistent with geologic observations along the margin. For example, the presence of Cyprus slab, as imaged by topography (e.g., Bakırcı et al, 2012;Abgarmi et al, 2017), is compatible with the location of the area of maximum crustal thicknesses and uplift (Fig. 3), hence solving the discrepancy inherent to slab break-off models (e.g., Schildgen et al, 2014).…”
Section: Forearc High Uplift In South Turkey and Other Settingsmentioning
confidence: 86%
See 1 more Smart Citation
“…We favor a model where lithosphere thinning is possibly related to a proposed SE dipping paleosubduction beneath the southern Kirsehir Massif and the Taurides (Figure ). The presence of the associated cold slab in the upper mantle seems to be imaged by regional tomography models (Bijwaard & Spakman, ; Piromallo & Morelli, ) (Figures a and b), and its possible presence is neither supported nor rejected by a recent RF study (Abgarmi et al, ). The proposed paleosubduction may (at the SW part) interact with the, still speculative, Cyprus subduction, therefore complicating the geodynamic evolution of southern Turkey and possibly channeling mantle melting associated with the Cyprus subduction toward the Antalya block and along the East Anatolian fault (Figure d).…”
Section: Geodynamic Implicationsmentioning
confidence: 91%
“…Anatolia has been covered by a large number of regional seismic tomography models (Biryol et al, ; Govers & Fichtner, ; Lei & Zhao, ; Maggi & Priestley, ; Portner et al, ; Salaun et al, ; Zor, ) and by some seismic RF studies (Abgarmi et al, ). Based on S ‐RF, the lithosphere thickness increases eastward from ~80 km in western Turkey to ~100 km beneath the East Anatolian Plateau (Kind et al, ), in overall agreement with our results that also show a general trend in lithosphere thickening eastward.…”
Section: Lithosphere Thermal Structurementioning
confidence: 99%